2023
DOI: 10.1039/d2cp04389k
|View full text |Cite
|
Sign up to set email alerts
|

Anion effect on the redox properties of copper ions in ionic liquids and deep eutectic solvents

Abstract: It has long been claimed that the anion of the DES or IL is critical for controlling the redox properties of metal ions. In this study we investigate the effect...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In [BMIM]­BF 4 , it was reported that the solubility of CuCl 2 ·2H 2 O is small, and the Cl – primarily coordinated the Cu 2+ cations using an X-ray adsorption spectroscopy measurement . For the electrodeposition of Cu 2+ in ILs, CVs were measured for a range of imidazolium-based ILs with various anions and different coordination strengths . CVs exhibit different redox properties depending on the anion species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [BMIM]­BF 4 , it was reported that the solubility of CuCl 2 ·2H 2 O is small, and the Cl – primarily coordinated the Cu 2+ cations using an X-ray adsorption spectroscopy measurement . For the electrodeposition of Cu 2+ in ILs, CVs were measured for a range of imidazolium-based ILs with various anions and different coordination strengths . CVs exhibit different redox properties depending on the anion species.…”
Section: Resultsmentioning
confidence: 99%
“…a range of imidazolium-based ILs with various anions and different coordination strengths 49. CVs exhibit different redox properties depending on the anion species.…”
mentioning
confidence: 99%
“…123 When using ionic uids to dissolve metal oxides, one of the critical parameters to metal solvation is the anionic component of the system. 124,125 However, the downsides to these systems is the high viscosity [126][127][128] and inevitably higher material costs relative to aqueous media. If ILs or DESs are to be used, care must be taken to ensure that the 'green' credentials are not overstated, and that the economic benets are maximised, either by a decrease in the energy needed for the process, reducing the amount of chemical additives required, or through the processing of small, concentrated amounts of high value materials.…”
Section: State Of the Art Of The Recycling Techniquesmentioning
confidence: 99%
“…Ionic liquids (ILs) and deep eutectic solvents (DESs) are lauded as novel solvents for metal processing due to their low water content and the ability to control speciation. [1] Recent work has confirmed that metal speciation and electrochemistry is controlled by the solvent anion, [2] and that the presence of small amounts of water (<10 wt %) does not affect the species present. [ 3 , 4 , 5 ] The original definitions of ionic liquids and DESs[ 6 , 7 , 8 , 9 ] do not appear to be helpful and a recent overview suggested that there is a continuum spanning ionic liquids, protonic ionic liquids, DESs, salt hydrates and brines.…”
Section: Introductionmentioning
confidence: 99%